Determinants of financial adequacy: Evidence from Malaysian Tamil schools - Kenayathulla, Husaina Banu; Subramaniam, Ranjeetham; A. Ghani, Muhammad Faizal; Abdullah, Zuraidah (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
Financial provision in education is one of the key factors contributing to the successful implementation of education programs in school. Financial management includes efficient management of school financial resources. However, the lack of financial resources affects students' achievement. Schools often encounter problems in providing the facilities needed by students. Schools receive financial resources in terms of per capita grants, public contributions and other government assisted funds such as scholarships and food supplements. The purpose of this study is to determine the adequacy of financial resources assigned to the National Type Tamil schools which are based on enrolment. This study was conducted in 30 National Type Government Tamil Schools and 16 National Type Government Assisted Tamil Schools in the State of Perak, Malaysia. A total of 276 respondents were involved in this survey. A logistic regression test was used to analyse factors contributing to the adequacy of financial provision for subjects, library, guidance and counselling and recurring expenditures. The findings indicate that policy makers should consider other factors such as socio-economic status and the type of schools in determining school funding allocation. Thus, the funding formula should not just be based on student enrolment.